Development of Hand Hygiene Audit Information System at Haji Public Hospital of Surabaya - Rezkha Mala Ludyaningrum; Arief Hargono; Arief Wijaya Rosli (Humanistic Network for Science and Technology (HNST), 2018)
Hand hygiene is the act of washing hands using antiseptic or handwash. Implementation of improper hand hygiene is a major cause of HAIs events and the spread of multi-resistant microorganisms in health facilities. WHO states that handwashing compliance can reduce the transmission of microorganisms by 20-40%. This activity aim to identify the type of information needed and the utilization of data on ouput components, processes, and inputs. The method used was descriptive observasional that aims to design the model of system development through data collection by indepth interview using interview guides and documentation studies to key informants and described in the form of DFD diagram. The results of activities in the form of information type needs in the output component include the identification of data that was not yet available on the information system that was running and the development plan of monthly report on the achievement of minimum service standards; process components include daily data collection manually and processed using Microsoft Excel; input components included data collection forms and hand hygiene audit compliance figures. It is recommended to test the information system that has been developed for each room, conduct questionnaires for patient training, and conduct routine monitoring and supervision by the head of the room. Keywords: Hand hygiene audit, Information system development, Infection control